The Effects of Machinima on Communication Skills in Students with Developmental Dyslexia - Nikolaos Pellas; Athanasios Christopoulos (MDPI AG, 2022)
Many research efforts in the international literature have been conducted to investigate various fundamental issues associated with communication skills cultivation of students with developmental dyslexia. However, little is known when it comes to the impact that 'immersive technologies', such as three-dimensional virtual worlds, without considering any exploration of their impact to assist boys and girls with developmental dyslexia cultivate communication skills. Motivated by this inadequacy in the literature, the purpose of this study is to explore the effectiveness of the machinima approach, created via OpenSimulator and Scratch4SL, for students with developmental dyslexia in vocabulary learning and practicing. This embedded mixed-methods research was conducted over a four-week timetable in-class course, with forty students (n = 40) aged 10-12 years old. All students were equally separated into two groups in line with their gender. Boys and girls were encouraged to unfold the communication skills developed (i.e., spelling, writing, reading) by creating their own stories, after viewing educational videos and machinima scenes, before and after the treatment. The results indicate that machinima positively affected students' learning outcomes and achievements. Machinima can improve immediate knowledge gains in boys compared to girls to purposefully translate their cognitive thinking into storytelling, when problem-solving situations through simulated realism are considered. This study also offers insights for educational implications and design guidelines for machinima creation, providing empirical evidence on its effect on the participants' linguistics understanding and communication skills for language learning in girls and boys with developmental dyslexia.